Managerial Perception of CSR: A Study of MNCs - Singh, Rajinder; Narwal, Mahabir (Prabandhan: Indian Journal of Management, 2010)
What does one perceive from the term business? Most commonly, business is defined as an economic activity undertaken for the purpose of making profits. No doubt, the main criterion to measure the performance of any business is the quantum of its profits. The more the profit, the more successful is perceived the business, so the corporate world is always engaged in the activities that lead to the maximization of their profits. It is obvious that the owners of the business, who provide their funds to be used in business have the right to have some return on their investment and they want the return to be maximum. But the situation becomes critical when the corporate world forgets that there are some other people also associated with the business and are affected by its activities. These people are consumers, employees, creditors, government and society in general which are collectively called stakeholders. The business has some responsibilities towards these stakeholders and this responsibility of business is called corporate social responsibility (CSR).The concept of CSR was visualized during the early part of the twentieth century. Clark (1916) was among the pioneers to observe that if men are responsible for the known results of their actions, business responsibilities must include the known results of business dealings, whether or not law has recognized these. CSR involves a range of concepts, principles, methodologies and a large diversity of empirical analysis. In recent years, the concept of CSR has gained a prominent significance, both in popular media and among academics.